Investigators Obstacles in Child Molestation Cases - Siti Nurhayati Nasir (Universitas Negeri Gorontalo, 2022)
Abstract: The purpose of this research is to identify the types of obstacles that investigators face when investigating child abuse. Empirical research approach was applied in this study. This study employs a qualitative methodology, purposive sampling, and descriptive qualitative analytic approaches. According to the findings of this study, the investigator's restrictions in processing instances of criminal acts of sexual abuse against minors are both internal and external. The internal barrier consists of people resources from investigators, the system, and the cultural side. Meanwhile, there are no witnesses to see, the victims are still minors, fees, and parents' inexperience of legal procedures. The execution of law enforcement investigations must boost confidence so that all types of hurdles to conducting investigations may be rapidly overcome. As a result, the inquiry is progressing as we all hoped. The investigation should be conducted in line with the appropriate legal procedure, particularly when dealing with cases of child abuse and updating legal knowledge for investigators, particularly those whose education is still insufficient.